Case report of sclerochoroidal calcification - A. D. Chuprov; V. I. Sinkova; A. R. Subkhankulova; I. A. Baryshnikov (Acta Biomedica Scientifica, 2023)
Background. Sclerochoroidal calcification is an idiopathic rare benign lesion of the sclera or choroid characterized by histological deposition of calcium pyrophosphate. Taking into consideration its similar clinical manifestations with other diseases of the sclera, the most dangerous of which are malignant, timely verification of the diagnosis with the appointment of a further observation period is important.The aim. The description of a clinical case of sclerochoroidal calcification to improve the efficiency of disease detection through the use of multimodal diagnostics.Material and methods. A 62-year-old patient with complaints of “bright flashes” in her left eye for the past few months, who underwent a standard complex of ophthalmological examinations, supplemented according to indications by optical coherence tomography of peripapillary nerve fibers, macular zone, B-scan, Dopplerography in color Doppler mapping mode. Auxiliary diagnostic methods were magnetic resonance imaging of the orbits and extraocular muscles, computed tomography of the orbits and a biochemical blood test.Results. Considering the anamnesis, the absence of progression of complaints, the data of instrumental diagnostic methods, the absence of pathological blood flow in the area of both eyes formations, the correct diagnosis is most likely to be sclerochoroidal calcification of both eyes, despite the difficulties of the diagnostic process, which consisted in the absence of visualization of foci during ophthalmoscopy.Conclusion. Sclerochoroidal calcification is of interest to practicing ophthalmologists due to the difficulties of diagnostic search and differential diagnosis with malignant neoplasms. Modern medicine has a sufficient set of instrumental and laboratory research methods for making an accurate diagnosis.